I'm practicing logical equivalence and I've come across a question that I'm struggling to answer:
Show that (R or P -> R or Q) is equivalent to (not R -> (P -> Q)).
I've examined the truth tables of both implications but the question states that I should use equivalence laws to show that the implications are equivalent.
If anyone could help me out, I would appreciate it.
Thank you.
Intuitive
A formal proof (included below) which only allows one to follow the steps one by one is less useful than a proof that helps us understand why both expressions are equivalent. Consider the first expression:
and think about its meaning...
The expression is trivial when
R=true
, isn't it? Therefore the only information it encloses is that whenR=false
,P -> (R or Q)
. But whenR=false
,(R or Q) = Q
. So, the precise meaning of the expression is that whenR=false
,P -> Q
. In other words,not R -> (P -> Q)
.Formal